141k views
0 votes
Follow the instructions below.5 2Writer ·x without exponents.+00.05 2X - XХ$Fių in the blank.52. X = X

Follow the instructions below.5 2Writer ·x without exponents.+00.05 2X - XХ$Fių in-example-1
User Vipin
by
6.2k points

1 Answer

4 votes

Answer:

x · x · x · x · x · x · x

5+2

Given:


x^5\cdot x^2

We can expand this as:


\begin{gathered} x^5=x\cdot x\cdot x\cdot x\cdot x \\ x^2=x\cdot x \\ \end{gathered}

Therefore:


\begin{gathered} x^5\cdot x^2=(x\cdot x\cdot x\cdot x\cdot x)\cdot(x\cdot x) \\ =x\cdot x\cdot x\cdot x\cdot x\cdot x\cdot x \end{gathered}

Now, according to the Product Rule of Exponents:


a^x* a^y=a^(x+y)

Applying this to our expression:


x^5\cdot x^2=x^(5+2)

User Didil
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.